NUTRITION REQUIREMENT OF CULTURED ABALONE POST LARVAE AND JUVENILES: A REVIEW - Wa Iba (Indonesian Aquaculture Journal, 2008)
Abalone aquaculture attracts wide attention nowadays because of its high market value and depleted of wild stocks. China and Japan are the main producer of abalone from aquaculture followed by other countries such as New Zealand, Australia and US. Most of cultured abalone are temperate species but considerable research efforts have been made to culture tropical abalone in the Philippines, Thailand, and Indonesia. Most of abalone culture still depends on natural food but recent studies have been conducted to develop artificial diet for abalone. This will not only reduce wild harvest of macrolagae but also develop high nutrition diet at low cost. Successful abalone aquaculture is determined by correct nutrition supplement in the diet. As other cultured animal, abalone requires balanced nutrition of carbohydrate, protein, lipid, vitamins, and minerals. As herbivores, abalone can utilize carbohydrate efficiently as energy source and thus only requires low level of protein (range from 27%—40%). Lipid requirements range from 3%—5% while some minerals such as calcium and phosphorus in artificial feed are only needed in small amount, 0.5% of calcium in diets and 0.7% of phosphorus in the diet can improve the growth rate of abalone. There is not available information of vitamin upplementation in the diet but it is suggested that natural food meets the requirement.